Mysterious ginger: Enclaves of a boom crop in Thailand - Sukanlaya Choenkwan (Forest and Society, 2017)
Ginger (Zingiber officinale) is a perennial herb revered as one of the most popular and valued spices of the world. Ginger is the main cash crop supporting the livelihood and improving the economic level of many ginger growers of India, Indonesia, Nigeria and Bangladesh. Although Thailand was the fifth highest ginger producing country in the world, documentation and general recorded information on ginger cultivation, both for domestic production and export value trade, is very limited. The ginger production system is also confounding. Moreover, ginger in Thailand has received little attention from researchers. There is no research or publications about Thai production of ginger and ginger farmers in both Thai and English publications. This paper is an initial attempt to establish a ginger story in Thailand by using the Plaba sub-district in Loei province as a case study to document this overlooked story and bring attention from researchers or government officials who are interested in the possibility of identifying new agriculture possibilities and recognize potential crops for further development to support rural livelihoods.